2013
DOI: 10.7314/apjcp.2013.14.3.2037
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Serum SELDI-TOF-MS Analysis in the Diagnosis of Early Lung Cancer

Abstract: Background: Different methods of diagnosis have been found to be inefficient in terms of screening and early diagnosis of lung cancer. Cancer cells produce proteins whose serum levels may be elevated during the early stages of cancer development. Therefore, those proteins may be recognized as potential cancer markers. The aim of this study was to differentiate healthy individuals and lung cancer cases by analyzing their serum protein profiles and evaluate the efficacy of this method in the early diagnosis of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Another relevant aspect is represented by the sample preparation protocols, as standard processing procedures to avoid modification or degradation of protein biomarkers are essential. [93] This issue has been investigated in two studies, [48,50] employing the same MS-technology and type of sample source, but different protocols of protein enrichment and processing. The studies [48,50] identified different proteins present in tumor patients compared to control subjects, underlining that the variability of proteomics results can depend not only on patient differences, but also on the lack of protocol standardization.…”
Section: Sample Handling and Storagementioning
confidence: 99%
“…Another relevant aspect is represented by the sample preparation protocols, as standard processing procedures to avoid modification or degradation of protein biomarkers are essential. [93] This issue has been investigated in two studies, [48,50] employing the same MS-technology and type of sample source, but different protocols of protein enrichment and processing. The studies [48,50] identified different proteins present in tumor patients compared to control subjects, underlining that the variability of proteomics results can depend not only on patient differences, but also on the lack of protocol standardization.…”
Section: Sample Handling and Storagementioning
confidence: 99%
“…This characteristic limits the application of genomics and transcriptomics for platelet study, while rendering proteomics a more suitable approach for evaluating platelets in both physiological and pathological conditions [17][18][19][20]. Surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) is a powerful technology in proteomic studies and has been explored for screening of various cancer biomarkers and disease diagnosis [21][22][23][24]. With continuous development of MS-based proteomics and protein isolation methodology, the field of platelet proteomics has attracted more and more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a number of peaks that we identified, for example, the peaks M/Z 1205and 4279, were not recognized previously. 32,33 This is conceivably due to the different experimental procedures used in the studies. Moreover, the varying approaches in data analysis may also contribute to the difference.…”
Section: Discussionmentioning
confidence: 99%